Interleaved Electroactive Molecules into LDH Working on Both Electrodes of an Aqueous Battery-Type Device - Julien Sarmet; Fabrice Leroux; Christine Taviot-Gueho; Patrick Gerlach; Camille Douard; Thierry Brousse; Gwenaëlle Toussaint; Philippe Stevens (Molecules, 2023)
By selecting two electroactive species immobilized in a layered double hydroxide backbone (LDH) host, one able to act as a positive electrode material and the other as a negative one, it was possible to match their capacity to design an innovative energy storage device. Each electrode material is based on electroactive species, riboflavin phosphate (RF) on one side and ferrocene carboxylate (FCm) on the other, both interleaved into a layered double hydroxide (LDH) host structure to avoid any possible molecule migration and instability. The intercalation of the electroactive guest molecules is demonstrated by X-ray diffraction with the observation of an interlayer LDH spacing of about 2 nm in each case. When successfully hosted into LDH interlayer space, the electrochemical behavior of each hybrid assembly was scrutinized separately in aqueous electrolyte to characterize the redox reaction occurring upon cycling and found to be a rapid faradic type. Both electrode materials were placed face to face to achieve a new aqueous battery (16C rate) that provides a first cycle-capacity of about 7 mAh per gram of working electrode material LDH/FCm at 10 mV/s over a voltage window of 2.2 V in 1M sodium acetate, thus validating the hybrid LDH host approach on both electrode materials even if the cyclability of the assembly has not yet been met.